Interactions of organophosphate flame retardants with human drug transporters - Valentin Tastet; Marc Le Vée; Marie Kerhoas; Anna Zerdoug; Elodie Jouan; Arnaud Bruyère; Olivier Fardel (Ecotoxicology and Environmental Safety, 2023)
Organophosphate flame retardants (OPFRs) are environmental pollutants of increasing interest, widely distributed in the environment and exerting possible deleterious effects towards the human health. The present study investigates in vitro their possible interactions with human drug transporters, which are targets for environmental chemicals and actors of their toxicokinetics. Some OPFRs, i.e., tris(2-butoxyethyl) phosphate (TBOEP), tris(1,3-dichloroisopropyl) phosphate (TDCPP), tri-o-cresyl phosphate (TOCP) and triphenyl phosphate (TPHP), were found to inhibit activities of some transporters, such as organic anion transporter 3 (OAT3), organic anion transporting polypeptide (OATP) 1B1, OATP1B3, organic cation transporter 2 (OCT2) or breast cancer resistance protein (BCRP). These effects were concentration-dependent, with IC50 values ranging from 6.1 µM (for TDCPP-mediated inhibition of OCT2) to 51.4 µM (for TOCP-mediated inhibition of BCRP). OPFRs also blocked the transporter-dependent membrane passage of endogenous substrates, notably that of hormones. OAT3 however failed to transport TBOEP and TPHP. OPFRs additionally repressed mRNA expressions of some transporters in cultured human hepatic HepaRG cells, especially those of OAT2 and OCT1 in response to TOCP, with IC50 values of 2.3 µM and 2.5 µM, respectively. These data therefore add OPFRs to the expanding list of pollutants interacting with drug transporters, even if OPFR concentrations required to impact transporters, in the 2–50 µM range, are rather higher than those observed in humans environmentally or dietarily exposed to these chemicals.